Cost analysis of various branded versus generic chemotherapeutic agents used for the treatment of early breast cancer- a deep insight from India. (3rd July 2020) - Kashyap, Ananth; Balaji, M N; Chhabra, Manik; Rashid, Muhammed; Muragundi, Pradeep M
ABSTRACT: Background: Breast cancer (BC) stands first with high incidence and mortality in India. Most of the oncologists are unaware of cost savings by utilising generic drugs. Aim: To perform a cost minimization analysis of generic versus branded chemotherapeutic regimen for treatment of BC. Methodology: CIMS (current index of medical stores) was referred for the cost of branded drugs and the generic cost was taken from Jan Aushadhi scheme. The percentage cost variation and potential cost-saving particular to BC regimens on substituting available generic drug was calculated using standard formula and costs were presented in Indian Rupees and US Dollars (as of 2019). Results: Among the branded agents considered, a range of 25% to 606.11% cost variation was observed with cyclophosphamide and 5-Fluorouracil respectively. Gemcitabine proposed the highest cost variation (373.68%-990.78%) and cyclophosphamide (71.42%-114.28%) with the lowest variation when compared to generic drugs. The highest level of cost-saving (₹60, 807.3 to ₹1, 31, 864.1) with TAC regimen and the lowest range (₹12, 15.84 to ₹15, 667.2) with AC regimen was observed among adjuvant therapy regimens. Conclusion: Our evaluation inferred that substituting generic chemotherapeutic drugs can bring potential cost savings. Healthcare professionals and patients should aware and opt generic drugs to achieve goals of BC therapy.